2017
DOI: 10.1186/s13071-017-2209-2
|View full text |Cite
|
Sign up to set email alerts
|

Ancylostoma ailuropodae n. sp. (Nematoda: Ancylostomatidae), a new hookworm parasite isolated from wild giant pandas in Southwest China

Abstract: BackgroundHookworms belonging to the genus Ancylostoma (Dubini, 1843) cause ancylostomiasis, a disease of considerable concern in humans and domestic and wild animals. Molecular and epidemiological data support evidence for the zoonotic potential among species of Ancylostoma where transmission to humans is facilitated by rapid urbanization and increased human-wildlife interactions. It is important to assess and describe these potential zoonotic parasite species in wildlife, especially in hosts that have physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 75 publications
1
15
0
2
Order By: Relevance
“…Meanwhile, Cryptosporidium spp. ( Wang et al, 2015 ), Ancylostoma ailuropodae ( Xie et al, 2017 ), Ogmocotyle sikae , Toxascaris seleactis , and Strongyloides spp. ( Zhang et al, 2011 ) have also been reported to cause parasitic infection in GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Cryptosporidium spp. ( Wang et al, 2015 ), Ancylostoma ailuropodae ( Xie et al, 2017 ), Ogmocotyle sikae , Toxascaris seleactis , and Strongyloides spp. ( Zhang et al, 2011 ) have also been reported to cause parasitic infection in GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar problems may be exacerbated in attempts to perform species-specific identification among certain wild animal-derived species. Species of Toxocara and Toxascaris in wild canids and felids are considered not only because these wildlife hosts may have recently adapted to the human-environment due to rapid urbanization leading to increased interactions with people in conservation centers and zoological gardens, but also because little attention has been paid to these ascaridoids due to the limited access to samples [ 2 , 38 41 ]. Such situations would negatively affect their diagnosis and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…and Uncinaria spp. have been observed in free‐ranging black and brown bears in North America, brown bears in Eastern Europe and giant pandas in China (Aghazadeh et al, ; Catalano, Lejeune, Paridon, et al, ; Catalano, Lejeune, Tizzani, et al, ; Xie, Hoberg, Yang, Urban, & Yang, ). Ova consistent with the Ancylostomatidae family, under which Ancylostoma spp.…”
Section: Helminth Zoonosesmentioning
confidence: 98%